2016
DOI: 10.5713/ajas.16.0046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microbial enzymes on starch and hemicellulose degradation in total mixed ration silages

Abstract: ObjectiveThis study investigated the association of enzyme-producing microbes and their enzymes with starch and hemicellulose degradation during fermentation of total mixed ration (TMR) silage.MethodsThe TMRs were prepared with soybean curd residue, alfalfa hay (ATMR) or Leymus chinensis hay (LTMR), corn meal, soybean meal, vitamin-mineral supplements, and salt at a ratio of 25:40:30:4:0.5:0.5 on a dry matter basis. Laboratory-scale bag silos were randomly opened after 1, 3, 7, 14, 28, and 56 days of ensiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 30 publications
4
23
0
4
Order By: Relevance
“…These microorganisms have their activity intensified in the presence of soluble carbohydrates, acids, and proteins, increasing the silage pH (Table 4). The hemicellulose degradation has been neglected for many years (Ning et al, 2017), but some studies have shown this degradation occurs during the ensiling (Muck, 1990;Chen et al, 2015). Melvin (1965) and Yahaya et al (2001) reported that the degradation products of hemicellulose (xylose) and starch (glucose) could be substrates for microorganisms to produce acids during the ensiling; this fact was observed in our study (Table 2).…”
Section: Discussionsupporting
confidence: 62%
“…These microorganisms have their activity intensified in the presence of soluble carbohydrates, acids, and proteins, increasing the silage pH (Table 4). The hemicellulose degradation has been neglected for many years (Ning et al, 2017), but some studies have shown this degradation occurs during the ensiling (Muck, 1990;Chen et al, 2015). Melvin (1965) and Yahaya et al (2001) reported that the degradation products of hemicellulose (xylose) and starch (glucose) could be substrates for microorganisms to produce acids during the ensiling; this fact was observed in our study (Table 2).…”
Section: Discussionsupporting
confidence: 62%
“…4). Bacillus pumilus can produce microbial enzymes that degrade plant structural carbohydrates during silage fermentation 38 . Furthermore, B. sonorensis was expected to be a potential source of endo‐glucanase and xylanase, which have potential applications in the saccharification of lignocellulosic biomass 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported B. amyloliquefaciens , B. cereus , B. licheniformis , B. subtilis , B. flexus and B. pumilus as the main sources of microbial enzymes that degrade complex carbohydrates in mixed‐feed silage plants during fermentation (Ning et al . 2017).…”
Section: Introductionmentioning
confidence: 99%